2014
DOI: 10.1161/circimaging.113.001317
|View full text |Cite
|
Sign up to set email alerts
|

Complex Left Atrial Appendage Morphology and Left Atrial Appendage Thrombus Formation in Patients With Atrial Fibrillation

Abstract: Background-In patients with atrial fibrillation (AF), most thrombus forms in the left atrial appendage (LAA). However, the relation of LAA morphology with LAA thrombus is unknown. Methods and Results-We prospectively enrolled 633 consecutive patients who were candidates for catheter ablation for symptomatic drug-resistant AF. Transesophageal echocardiography (TEE) was performed to assess LAA thrombus. LAA structure was assessed by 3-dimensional TEE. LAA orifice area, depth, volume, and number of lobes were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(109 citation statements)
references
References 28 publications
6
95
1
4
Order By: Relevance
“…An increased number of lobes was associated with the presence of a thrombus independent of the clinical risk [18]. The "cauliflower" morphology is most often associated with embolic events.…”
Section: Anatomy Of Left Atrial Appendagementioning
confidence: 94%
“…An increased number of lobes was associated with the presence of a thrombus independent of the clinical risk [18]. The "cauliflower" morphology is most often associated with embolic events.…”
Section: Anatomy Of Left Atrial Appendagementioning
confidence: 94%
“…In a Japanese study of 564 patients with 3D-TEE, left atrial volume and number of LAA lobes were independently associated with LAA thrombus, with 94% (32/34) of those with thrombus having 3 or more lobes. 98 In contrast, LAA ostial size has been associated with both an increased 32 and decreased 97 …”
Section: Left Atrial Appendage Morphology and Microstructure Complexitymentioning
confidence: 98%
“…Previous studies have shown that non-paroxysmal AF [35], LAE [5,18,21,[36][37][38][39][40], and impaired LVEF [35][36][37][38][39] were independent risk factors for LAT/SEC. Consistent with these observations, clinical studies or meta-analysis using thromboembolic events as the end point also showed that non-paroxysmal AF increased risk for AFrelated thromboembolism [41], and that LAE [42,43] and impaired LVEF [42,44] were the independent predictors of thromboembolic events.…”
Section: Association Of Thromboembolic Riskmentioning
confidence: 99%